Komposisi Jenis dan Struktur Vegetasi Hutan Gambut Di Desa Tumbang Bulan Taman Nasional Sebangau : Type of Composition and Structure of Vegetation in Peat Swamp Forest In Tumbang Bulan Village Sebangau National Park - Setiarno; Laksana Atyasa; Muhammad Luthfi S. (HUTAN TROPIKA, 2022)
Landfire is one of the main factors of peat forest degradation. This work aims to look for species composition, vegetation structure, and post-fire species diversity. This research is situated in a peat forest area at an administrative zone of Desa Tumbang Bulan, around Sebangau National Park of Central Kalimantan being burned in 2015. The research is conducted using a quadratic plot. The observed parameter includes the species composition of stand structure and its ecology characteristics, i.e. Diversity Index, Richness Index, Evenness Index, and Similarity Index. The result showed the vegetation species in the research site are 101 species classified into 52 families which spread in many levels, i.e. seedling, sapling, pole, tree, and bottom plant. Pandanus sp. and Combretocarpus rotundatus are among the species of tree and bottom plant habitat with the highest NPJ. The index diversity, species richness, and evenness of this habitat range from low to high index value, while the inter-site and inter-growth levels of community similarity are low in general. The horizontal stand structure in the research site had a different exposed diameter that resembles the upside down of the "J" curve and concentrated on 10-<20 cm class diameter. Kata kunci (Keywords): Peat Swamp Forest, species composition, vegetation structure, growth